Estándares de calidad ambiental, su forma de cumplimiento en los estudios de impacto ambiental aprobados por PRODUCE, entre los años 2016 - 2021 - Espinoza Eche, José Jorge (2023)
Article 31 of Law No. 28611 establishes that the Environmental Impact Studies (EISs) must conclude that there is no breach of the Environmental Quality Standards (EQSs); likewise, taking into account that the EQSs have a numerical expression, it would be expected that the objective way of concluding that they are not breached is also a numerical expression, otherwise a conclusion based on other ways not related to the contrast of the numerical value, would lead to a subjective appreciation. The purpose of the investigation consisted in determining the predominant way, through which the conclusion has been reached that the EQSs are not breached, in the approved EISs. For this purpose, a logical sequence of five (05) steps was developed to identify the applicable ECAs, the emissions or discharges, the concentration in the receiving body, the contrast with the EQSs and the manner of compliance, which allowed to be able to qualify these conclusions as subjective or objective. Based on this evaluation, it was determined that the way to conclude that the applicable EQSs are not breached is 40% objective, and 60% subjective, the latter form of conclusion being the predominant one.